Earnings Management and the Floatation Structure: Empirical Evidence from Polish IPOs - Tomasz Sosnowski (Institute of Economic Research (IER), 2017)
Firms use discretionary accounting choices to manage earnings disclosures around the time of certain types of corporate events. The IPO provides an opportunity to earnings management because of the significant information asymmetry between investors and issuers at the time of the offering. The main aim of the study is to empirically investigate the links between the earnings management and the portions of primary and secondary shares sold in IPO. In order to investigate whether the earnings management influences the issue of new shares and the sale of secondary shares I use Tobit and logit regressions, where discretionary accruals are the proxy for earnings management. Using a sample of 221 firms from WSE between 2005 and 2015 I do not find evidence that the increase of pre-IPO discretionary accruals positively affects the sale of primary shares in the IPO, but the analysis revealed that the reporting less limits the probability of the new shares issuance. In turn, the sale of secondary shares in the IPO is more likely in companies using a conservative earnings management. Furthermore, negative discretionary accruals increase the portion of secondary shares in the IPO.
Keywords: G14; G32; G23; 330; Initial public offering; IPO; Primary shares; Secondary shares; Earnings management